2021
DOI: 10.1001/jamanetworkopen.2021.2373
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Disturbed Sleep and Depression in Children and Youths

Abstract: IMPORTANCE Disturbed sleep represents a potentially modifiable risk factor for depression in children and youths that can be targeted in prevention programs. OBJECTIVE To evaluate the association between disturbed sleep and depression in children and youths using meta-analytic methods. DATA SOURCES Embase, MEDLINE, PsycINFO, Scopus, Web of Science, and ProQuest Dissertations & Theses Global were searched for articles published from 1980 to August 2019. STUDY SELECTION Prospective cohort studies reporting estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 100 publications
3
35
0
1
Order By: Relevance
“…This study demonstrated the general association between short sleep, not engaging in physical activity, long screen time and general mental health problems. Although the evidence is stronger for the association between these lifestyle factors and specific mental health symptoms such as depression and anxiety [ 8 10 , 13 ], some previous studies demonstrated an association between lifestyle factors and general mental health problem [ 50 52 ]. This study suggested that multiple lifestyle factors contributed to poorer mental health, which imply that the needs of fostering healthy lifestyle among children are applicable to greater population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated the general association between short sleep, not engaging in physical activity, long screen time and general mental health problems. Although the evidence is stronger for the association between these lifestyle factors and specific mental health symptoms such as depression and anxiety [ 8 10 , 13 ], some previous studies demonstrated an association between lifestyle factors and general mental health problem [ 50 52 ]. This study suggested that multiple lifestyle factors contributed to poorer mental health, which imply that the needs of fostering healthy lifestyle among children are applicable to greater population.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that long screen time causes attention problems among children [ 11 , 12 ]. One meta-analysis reported that sleep loss is associated with depression [ 13 ]. According to another systematic review, physical inactivity, long sedentary time and short sleep together pose higher risk on children’s and adolescents’ depression [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in sleep duration in children has been associated with [55], poor mental health [56] and obesity [57]. Greater bed-time variability is associated with a less healthy pattern of lifestyle behaviors [5].…”
Section: Sleepmentioning
confidence: 99%
“…There is a growing body of literature that recognizes the importance of sleep disturbance and how it is related to adolescent depression. Several studies with a longitudinal design argue that impaired sleep affects the initiation, development, and maintenance of depression in adolescents [8][9][10][11]. In their meta-analysis, Lovato and Gradisar proposed a conceptual model to understand how lack of sleep leads to rumination, negative affect, hyperarousal, and emotional dysregulation, with subsequent depression and insomnia as a result [9].…”
Section: Introductionmentioning
confidence: 99%